Mid-upper arm circumference as a substitute of the body mass index for assessment of nutritional status among adult and adolescent females: learning from an impoverished Indian state. (February 2020) - Das, A.; Saimala, G.; Reddy, N.; Mishra, P.; Giri, R.; Kumar, A.; Raj, A.; Kumar, G.; Chaturvedi, S.; Babu, S.; Srikantiah, S.; Mahapatra, T.
Abstract: Objectives: For population-level screening of malnutrition among adults—especially in developing-country settings—the body mass index (BMI) can be impractical because of logistical requirements for weight and height measurement. We analyzed anthropometric data collected from a large-scale nutritional survey on women of rural Bihar to determine the mid-upper arm circumference (MUAC) cutoffs corresponding to standard BMI cutoffs and the predictive accuracies of the determined cutoffs. Study design: It was a cross-sectional study using multistage cluster sampling. Methods: The current analysis used anthropometric data from a study on dietary practices of rural women (adolescents, lactating mothers, and women in the interpregnancy period). The MUAC (cm) cutoffs corresponding to four standard BMI (kg/m 2 ) values were determined using receiver operating characteristic (ROC) curve analysis. Result: We detected a significant positive correlation between BMI and MUAC (r = 0.81, P < 0.0001). In ROC curve analysis, the MUAC cutoffs corresponding to BMI cutoffs of 18.5, 23, 25, and 30 kg/m 2 were estimated to be 23.2, 26.0, 27.3, and 30.5 kg/m 2, respectively. The predictive accuracy of the determined cutoffs was good, as indicated by the area under the ROC curve for the four different cutoffs—which ranged between 88% and 97%. Other than the cutoff for 'obese' (BMI, 30 kg/m 2 ), the Kappa coefficients for the rest of the MUAC cutoffs showed 'substantial' agreement (>0.6) with their BMI counterparts. Conclusion: The results suggest that the cutoffs based on MUAC—a less resource-intensive measure than BMI—can be used for community-based screening of malnutrition among women of Bihar. Highlights: Body mass index (BMI) is a widely used metric for assessing nutritional status among adults. However, it is difficult to assess in community settings because of logistical and technical challenges. Mid-upper arm circumference (MUAC) can be used in lieu of BMI. The present study detected the MUAC values corresponding to the standard BMI cutoff among rural Indian women.